1999
DOI: 10.1007/s004420050699
|View full text |Cite
|
Sign up to set email alerts
|

Can extreme morphology in Bosmina reduce predation risk from Leptodora ? An experimental test

Abstract: Bosmina (Cladocera) populations, especially within the subgenus Eubosmina, show a variety of phenotypes that exhibit large differences in body size and shape and antennule length. In some populations, the morphological traits also vary during the season, with the most extreme forms occurring in periods with high densities of certain invertebrate predators. However, while temporal phenotypic variation in other cladocerans, as in the family Daphnidae, has been shown to be an adaptation to reduce the risk of pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Late summer populations of Ceriodaphnia and Bosmina that overlap temporally with Leptodora were noticeably absent only 1 yr after the introduction. Hellsten and Stenson (1995) also observed a rapid disappearance of Bosmina longispina in a Swedish lake when Leptodora populations were dense. The rapid shift in size structure and near extirpation of several small-bodied cladoceran species following the introduction of Leptodora is comparable to that observed when Chaoborus colonizes a lake.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Late summer populations of Ceriodaphnia and Bosmina that overlap temporally with Leptodora were noticeably absent only 1 yr after the introduction. Hellsten and Stenson (1995) also observed a rapid disappearance of Bosmina longispina in a Swedish lake when Leptodora populations were dense. The rapid shift in size structure and near extirpation of several small-bodied cladoceran species following the introduction of Leptodora is comparable to that observed when Chaoborus colonizes a lake.…”
Section: Discussionmentioning
confidence: 79%
“…With an increase in Leptodora abundance, Bosmina became larger-bodied and the population shifted from short-featured (mucro, antennule length) to long-featured morphs. Bosmina morphs with long features have lower death rates and higher escape efficiencies than short-featured morphs (Hellsten et al 1999).…”
Section: Discussionmentioning
confidence: 92%
“…burrows in benthic species and larval cases in caddisflies. Immobilization and thanatosis are efficient against predators that rely on movement stimuli (Pritchard, 1965) and may also allow prey to confuse the predator and subsequently escape (Hellsten et al, 1999;Gyssels and Stoks, 2005;Scarton et al, 2009). Behavioural responses may vary between and within taxa; recent research has linked intraspecific variation in prey vulnerability and defensive behaviour to behavioural syndromes (Sih et al, 2004).…”
Section: Prey Vulnerability Traitsmentioning
confidence: 99%
“…Induced defences in cladoceran prey strongly influence the effectiveness of Leptodora attacks: "defended" forms of Bosmina spp. (Hellsten et al 1999) and Daphnia cucullata (Agrawal et al 1999) were shown to be much less vulnerable than the ones without defences, thus adaptive responses of Leptodora for changing prey morphology were expected.…”
Section: Introductionmentioning
confidence: 96%